2016
DOI: 10.1159/000442896
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Inhibition of Enamel Demineralization by Peptide 8DSS and Fluoride

Abstract: The biomimetic peptide 8DSS has shown beneficial effects in promoting remineralization of demineralized enamel in vitro. Here we examined the ability of 8DSS alone and in combination with fluoride to inhibit enamel demineralization during pH-cycling mimicking intraoral conditions. Enamel blocks were subjected to 9 days of pH-cycling in the presence of 1,000 ppm NaF (positive control), distilled-deionized water (DDW; negative control), 25 μM 8DSS alone, 25 μM 8DSS with 500 ppm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
1
13
0
3
Order By: Relevance
“…The newly grown mineral had uniform deposition of small apatite crystals with significantly improved properties such as reduced surface roughness, and higher hardness and elastic modulus [Chung et al, 2012;Hsu et al, 2011]. A recent in vitro study also provided strong evidence that the biomimetic 8DSS peptide, besides inhibiting enamel demineralization on its own, could significantly potentiate the ability of fluoride to do the same [Yang et al, 2016]. This synergistic interaction can be useful to lower fluoride concentration for caries prevention in young children reducing their risk of dental fluorosis.…”
Section: Biomimetic Remineralizationmentioning
confidence: 94%
“…The newly grown mineral had uniform deposition of small apatite crystals with significantly improved properties such as reduced surface roughness, and higher hardness and elastic modulus [Chung et al, 2012;Hsu et al, 2011]. A recent in vitro study also provided strong evidence that the biomimetic 8DSS peptide, besides inhibiting enamel demineralization on its own, could significantly potentiate the ability of fluoride to do the same [Yang et al, 2016]. This synergistic interaction can be useful to lower fluoride concentration for caries prevention in young children reducing their risk of dental fluorosis.…”
Section: Biomimetic Remineralizationmentioning
confidence: 94%
“…Yarbrough et al designed peptides with repeated aspartate‐serine–serine (DSS) sequences derived from dentin phosphoprotein to promote mineral deposition and bind to calcified surfaces (Yarbrough et al, 2010). In a more recent study, our group verified the remineralization ability of 8DSS peptide on incident enamel caries and its inhibitory effect on demineralization in vitro (Yang et al, 2014; Yang et al, 2016). Other biomimetic peptides derived from amelogenin have been investigated to study their effects on enamel formation, including a novel peptide designed by our group that included five repeated tandem amelogenin repeats of Gln‐Pro‐X and a hydrophilic tail (Han et al, 2017; Lv et al, 2015).…”
Section: Discussionmentioning
confidence: 87%
“…Demineralized enamel shows more porosity than sound enamel, which encouraged more penetration of the gel ion components, also showed larger surface area allowing better subsequent reaction of the enamel mineral (14) , these factors boosted the potential of nanohydroxyapatite to directly fill up the defects and micro-pores of the demineralized enamel (15) , also it allowed the precipitation of calcium from the coral calcium gel on the enamel surface as due to the high concentration of the calcium carbonate present in the coral calcium which leads to deposition of calcium ions by concentration gradient. S B Huang et al demonstrated that 10% nanohydroxyapatite showed a good effect on remineralization as increasing the concentration will lead to deposition of nanohydroxyapatite on the surface layer which would probably block the surface pores and restrict the diffusion into the lesion over short term of remineralization (16) .…”
Section: Discussionmentioning
confidence: 99%